The fungal and protist community as affected by tillage, crop residue burning and N fertilizer application - Dendooven, Luc; Pérez‑Hernández, Valentín; Gómez-Acata, Selene; Verhulst, Nele; Govaerts, Bram; Luna-Guido, Marco; Navarro–Noya, Yendi E. (Springer, 2025)
The bacterial community in soil is often affected by agricultural practices, but how they affect protists and fungi is less documented. Soil from treatments that combined different N fertilizer application rates, tillage and crop residue management was sampled from a field trial started by the International Maize and Wheat Improvement Center (CIMMYT) at the ‘Campo Experimental Norman E. Borlaug’ (CENEB) in the Yaqui Valley in the northwest of Mexico in the early 1990s, and the fungal and protist community determined. Tillage, residue burning, and N fertilizer application had no significant effect on the fungal and protists alpha diversity expressed as Hill numbers and no significant effect on the fungal and protist community structure considering all species. The relative abundance of plant pathogens and undefined saprotrophs as determined with FUNGuildR increased significantly with tillage, while that of dung-plant and dung-soil saprotroph, and plant pathogens by burning (P < 0.05). It was found that the protists and fungal community structures were not altered by different agricultural practices, but some fungal guilds were, i.e., plant pathogens and saprotrophs, which might affect soil organic matter decomposition, nutrient cycling and crop growth.